Pragmatic aspects of street protests discourse (on the example of protests in Belarus in 2020) - Kiklewicz, Aleksander (Przegląd Wschodnioeuropejski, 2023)
The author analyzes the pragmatic properties of protest discourse, taking into account poster slogans used during mass anti-government protests in Belarus in 2020. The theoretical basis of the research is the concept of discourse, based on four categories: intention, representation, performance and context. The author distinguishes among three types of contexts: cognitive, social and event-related (functional). In accordance with the global function of the protest discourse, three types of constitutive language activities are distinguished: modal-evaluative, modal-disapproving and speech acts of ultimatum. The author analyzes these types of speech acts in detail and provides numerous linguistic examples.